Quantum Field Theory in Curved Spacetime - Loso Judijanto; Bassam Al-Khouri; Rania Khatib (Journal of Tecnologia Quantica, 2025)
Quantum field theory and general relativity are the two main pillars of modern physics. However, the two still cannot be combined consistently to explain cosmic phenomena at the microscopic level, especially in the context of curved spacetime. This research aims to explore the interaction between quantum fields and the curvature of spacetime, with a focus on the implications of quantum gravity. This research aims to understand how quantum fields interact with curved spacetime, as well as to develop a more comprehensive model of physics that combines these two concepts. The methods used include the development of mathematical models and numerical simulations to integrate quantum field theory with general relativity. The analysis was carried out by examining the impact of space-time curvature on quantum field fluctuations around massive objects such as black holes. The findings show that the curvature of spacetime has a major influence on the behavior of the quantum field, leading to modifications in energy distribution and field fluctuations. This discovery opens up new possibilities in the development of a more complete theory of quantum gravity. This study provides new insights into understanding the relationship between quantum fields and curved spacetime, as well as opening the way for further research in the field of quantum gravity and extreme cosmic phenomena.